How to Validate in silico Deployment of Coronary Stents: Strategies and Limitations in the Choice of Comparator - Berti, Francesca; Antonini, Luca; Poletti, Gianluca; Fiuza, Constantino; Vaughan, Ted J.; Migliavacca, Francesco; Petrini, Lorenza; Pennati, Giancarlo (Frontiers in Medical Technology, 2021)
This study aims at proposing and discussing useful indications to all those who need to validate a numerical model of coronary stent deployment. The proof of the reliability of a numerical model is becoming of paramount importance in the era of in silico trials. Recently, the ASME V&V Standard Committee for medical devices prepared the V&V 40 standard document that provides a framework that guides users in establishing and assessing the relevance and adequacy of verification and validation activities performed for proving the credibility of models. To the knowledge of the authors, only a few examples of the application of the V&V 40 framework to medical devices are available in the literature, but none about stents. Specifically, in this study, the authors wish to emphasize the choice of a relevant set of experimental activities to provide data for the validation of computational models aiming to predict coronary stent deployment. Attention is focused on the use of ad hoc 3D-printed mock vessels in the validation plan, which could allow evaluating aspects of clinical relevance in a representative but controlled environment.